Effect of Grain Size Distribution on Frictional Wear and Corrosion Properties of (FeCoNi)86Al7Ti7 High-Entropy Alloys - Qinhu Sun; Pan Ma; Hong Yang; Kaiqiang Xie; Shiguang Wan; Chunqi Sheng; Zhibo Chen; Hongji Yang; Yandong Jia; Konda Gokuldoss Prashanth (Entropy)
Optimization of grain size distribution in high-entropy alloys (HEAs) is a promising design strategy to overcome wear and corrosion resistance. In this study, a (FeCoNi)86Al7Ti7 high-entropy alloy with customized isometric and heterogeneous structure, as well as fine-crystal isometric design by SPS, is investigated for microstructure, surface morphology, hardness, frictional wear, and corrosion resistance. The effects of the SPS process on the microstructure and mechanical behavior are elucidated, and the frictional wear and corrosion resistance of the alloys are improved with heterogeneous structural fine-grain strengthening and uniform fine-grain strengthening. The wear mechanisms and corrosion behavior mechanisms of (FeCoNi)86Al7Ti7 HEAs with different phase structure designs are elaborated. This work highlights the potential of using powder metallurgy to efficiently and precisely control and optimize the multi-scale microstructure of high-entropy alloys, thereby improving their frictional wear and corrosion properties in demanding applications.